2014
DOI: 10.1007/s11095-014-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteotropic Polypeptide Nanoparticles with Dual hydroxyapatite Binding Properties and Controlled Cisplatin Delivery

Abstract: These properties suggest the potential utility of cisplatin-loaded PBLG-b-PGlu nanoparticles as carrier systems for the treatment of bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Therefore, recent research on HA bioceramics focused on producing multifunctional materials, which, in addition to being used as scaffolds for growing tissue, could also release drugs directly into the bone in the affected area [14]. The literature describes research on HA as a delivery system for antiresorptive (e.g., bisphosphonates) and anticancer drugs (e.g., doxorubicin and cisplatin), as well as antibiotics mainly against perioperative and intraoperative infections [15][16][17].…”
Section: mentioning
confidence: 99%
“…Therefore, recent research on HA bioceramics focused on producing multifunctional materials, which, in addition to being used as scaffolds for growing tissue, could also release drugs directly into the bone in the affected area [14]. The literature describes research on HA as a delivery system for antiresorptive (e.g., bisphosphonates) and anticancer drugs (e.g., doxorubicin and cisplatin), as well as antibiotics mainly against perioperative and intraoperative infections [15][16][17].…”
Section: mentioning
confidence: 99%
“…For P(L‐Glu‐Bz)‐P(L‐Glu) conjugates with CDDP, the polymer and the conjugate adopted ellipsoidal shapes (aspect ratio of 1.3, 37 ± 7 nm × 27 ± 6 nm) with a hydrodynamic diameter of 49–58 nm. The authors observed no significant changes in the morphology with CDDP loading up to 8.3% …”
Section: Physico‐chemical Properties Driving the Bio‐nano Interfacementioning
confidence: 99%
“…The in vitro drug release studies showed that physiological concentrations of chloride ions triggered cisplatin release with a near zero‐order kinetics profile over 14 days 187 . The high affinity binding of cisplatin‐loaded PBLG‐b‐PGlu NPs to calcified matrix was also approved by an in vitro HA binding assay 187 …”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 99%